Habitus and Social Capital in Muhammadiyah Vocational Schools: Religious, Social, and Moral Formation - Parinda, Efi; Zarkasih, Z.; Zein, Mas’ud; Dewi, Eva; Ahmad, Nur Jahan (POTENSIA: Jurnal Kependidikan Islam, 2026)
This study examines how Muhammadiyah vocational schools in Pekanbaru, Indonesia, implement religious habituation programs to shape students’ re-ligiosity, moral character, and social attitudes through the formation of re-ligious habitus in everyday school life. Using a qualitative multiple-case study design, the research involved three Muhammadiyah vocational schools, with participants including school leaders, teachers, activity coordinators, and students. Data were collected through observations, semi-structured interviews, and document analysis, and analyzed thematically using Bourdieu’s concepts of habitus, field, and capital. The findings indicate that habituation practices such as congregational prayer, kultum (short religious talks), and charitable activities play varying roles in shaping students’ religious dispositions. Practices that are structurally integrated into daily routines and supported by teacher role modeling tend to foster more consistent and internalized behaviors. In contrast, activities that rely heavily on supervision often result in formal participation without deep personal engagement. For instance, students continue prayer practices even without strict monitoring, while participation in kultum declines when supervision is reduced. Overall, the study demonstrates that religious habitus formation is not uniform but varies depending on the degree of institutional integration, symbolic reinforcement, and pedagogical support. These findings highlight the importance of aligning habituation programs with curriculum structures and reflective pedagogical strategies to promote students’ religious autonomy.